A rare presentation of disseminated invasive aspergillosis - Banerjee, Rituparna; Patil, Smita; Pendse, Manish; Mukherji, Anannya; Kashyap, Prashant (International Journal of Research in Medical Sciences, 2017)
Here’s presenting a case of disseminated invasive aspergillosis in a young female patient with pulmonary and CNS complications and the difficulty one faces while diagnosing such a case due to variable presentation of symptoms with no prior history of any underlying immunodeficiency. It also focuses on how diagnosing such a case can be further delayed due to clinical and radiological miss-match. Thus, it is important to have a high index of suspicion in such patients as prolonged antibiotics and systemic steroids worsens the course of illness.